2012
DOI: 10.1007/s12291-012-0261-4
|View full text |Cite
|
Sign up to set email alerts
|

Usage of Conventional PCR Technology for the Detection of HLA-B27 Allele: A Significant Molecular Marker of Ankylosing Spondylitis

Abstract: Ankylosing spondylitis is a chronic inflammatory disease that has been linked to the human leukocyte antigen class I allele HLA-B27. More than 90 % of patients with ankylosing spondylitis possess the HLA-B27 allele, but only 1 % of people with HLA-B27 develop the disease. Ankylosing spondylitis predominately affects young males. The present study was planned to find out the involvement of HLA-B27 specific allele in relation to age and sex in symptomatic suspected patients of ankylosing spondylitis using conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…In two different studies held in Chinese population, Yi et al 20 reported a percentage of 93.3% of HLA-B27 positivity in 360 AS patients, while Xiong et al 21 reported a percentage of 90.7% in 350 AS patients. On the other hand, in the study conducted in India with a smaller sample size (n=40), Sharma et al 22 found a very low frequency of HLA-B27 allele positivity (30%) in AS patients. Similar to our findings, the HLA-B27 allele frequency in AS patients were found as 62.5% in Serbia, 69% in Qatar, and 71.7% in Iran populations.…”
Section: Discussionmentioning
confidence: 89%
“…In two different studies held in Chinese population, Yi et al 20 reported a percentage of 93.3% of HLA-B27 positivity in 360 AS patients, while Xiong et al 21 reported a percentage of 90.7% in 350 AS patients. On the other hand, in the study conducted in India with a smaller sample size (n=40), Sharma et al 22 found a very low frequency of HLA-B27 allele positivity (30%) in AS patients. Similar to our findings, the HLA-B27 allele frequency in AS patients were found as 62.5% in Serbia, 69% in Qatar, and 71.7% in Iran populations.…”
Section: Discussionmentioning
confidence: 89%
“…13 Serological techniques for HLA antigen detection include classic microcytotoxicity and flow cytometry. 19 Originally described by Terasaki and McClelland (1964), microcytotoxicity was long-established method for HLA typing, but cross-reactivity induced HLA-typing errors and labor intensiveness limited its further use. 20 Flow cytometry is a rapid and relatively inexpensive method for preliminary screening of HLA antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Excluding HLA‐B27 virtually excludes the possibility of ankylosing spondilytis . Serological techniques for HLA antigen detection include classic microcytotoxicity and flow cytometry . Originally described by Terasaki and McClelland (1964), microcytotoxicity was long‐established method for HLA typing, but cross‐reactivity induced HLA‐typing errors and labor intensiveness limited its further use .…”
Section: Discussionmentioning
confidence: 99%
“…DNA was extracted by salting out technique. The presence of HLA B27 was analyzed using ARMS-PCR by the previously described method [16]. CRP was measured by Nephelometry.…”
Section: Clinical Detailsmentioning
confidence: 99%